Relative Comprehensiveness of Performance Measurement System: Organisational Ownership Structure and Size - Rasit, Zarinah Abdul; Isa, Che Ruhana (Sciedu Press, 2019)
Change in the business environment has resulted in significant implication in the use of Management Control System (MCS) particularly Performance Measurement System (PMS). Strategic Performance Measurement System (SPMS) has been widely used by organisation to monitor the implementation, achievement and improvement of its plan objectives. Considerable prior research identified inconsistent findings in the relationship between PMS and organisational performance. In view of the fact that organisational culture would significantly being influenced by ownership structure, this research will further explore the comprehensiveness of PMS, the extent to which the systems provide information and integration with strategy and value chain, with different ownership structure. Data were gathered in two (2) phases; firstly, using the survey data administered to the 120 strategic business unit (SBU) managers of the manufacturing companies, members of the Federation of Malaysian Manufacturers (FMM). The second phase involves conducting semi-structured interviews with SBU managers of the 10 companies with foreign and local ownership structure. Findings from the research identified that more comprehensive PMS is being implemented by foreign owned companies rather than local own companies. The size of the companies may also influence the PMS comprehensiveness. The PMS implementation was also found to be influenced by the parent companies. Adequate information technology (IT) plays an important role for effective use of the PMS, provide added supports for performance assessment, communication and exchange of information within the organisation and inter-organisations worldwide. Findings provide significant insights into the organisational factors influence the PMS design. © Sciedu Press.